Pengaruh Variabel Makroekonomi Terhadap Hasil Investasi Pada Perusahaan Asuransi Syariah di Indonesia - Fitrian Aprilianto (Jurnal Ilmiah Ekonomi Islam, 2022)
This study aims to determine the macroeconomic variables that affect the investment returns of Islamic insurance. The research approach uses a quantitative approach with the type of associative research. The data source uses secondary data in the form of monthly data published by OJK and BI from 2014-2020. The data analysis technique used multiple regression analysis techniques. The result showed that the BI Rate, Exchange Rate, and the Jakarta Islamic Index had a significant effect on the investment returns of sharia insurance. On the other hand, inflation and the money supply have no significant effects.